Dampak Pendekatan STEAM terhadap Problem Solving Skill pada Proses Pembelajaran Matematika Pelajar - Jumalia, Jumalia; Danial, Danial; Tahmir, Suradi (Jurnal Pendidikan Matematika : Judika Education, 2026)
This research aims to determine the impact of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on the mathematics learning process on students' problem-solving abilities at various levels of education. This study is a literature review that collects and analyzes various studies related to the application of STEAM, which is often combined with project-based learning (PBL) and problem-based learning (PBL) models. The results of the study show that the implementation of STEAM consistently improves students' problem-solving skills significantly. Through STEAM, students are not only trained to solve problems mathematically, but also develop creativity, critical thinking, and the ability to collaborate and communicate in an interdisciplinary and authentic learning context. Digital learning media such as the Alef, Quizizz, and MONKABICO platforms, as well as STEAM-based digital worksheets, also support the effectiveness of learning. However, the study also found various limitations, such as limited sample coverage, short intervention time, variations in STEAM learning models, and uneven teacher and infrastructure readiness. It is recommended that future research focus on comparing the most effective STEAM learning models, developing comprehensive problem-solving measurement instruments, and conducting long-term research that considers the local context and student inclusivity. In conclusion, STEAM is a relevant and effective learning approach to improve students' problem-solving skills in mathematics, while preparing them for the 21st-century skills that are urgently needed in the era of globalization and the digitalization of education in the future.   Keywords: Mathematics, Problem Solving Skill, STEAM.